Standing and Crying Over the Ruins in the Poetry of Arab Women Poets from the Pre-Islamic Era to the Abbasid Era: . - Mawlood , Hafssat Najm (Zanco Journal of Human Sciences, 2024)
Standing on the ruins and crying home was one of the distinct features that were known by the introductions to pre-Islamic poetry poems, and it became a tradition followed by most poets, and poets continued it in the era of early Islam, the Umayyad era and the Abbasid era, poets stood on the ruins and mentioned the old homes and mentioned the beloved, although some of them had abandoned those environments that led to this tradition, women in their poetry followed the traditions of standing on the old homes with many verses for her You stand in it on the ruins. This study reveals the poems in which the poets stood in the ancient era on the ruins and crying home and spinning, and the reasons for the emergence of this phenomenon in their poetry through the extrapolation of these poems following the descriptive analytical approach, in the pre-Islamic era the poets were most of them were starting their poetry directly with the purpose of poetry basis, which was lamentation, due to being affected by the greatness of the tragedy, or because most of their poetry was in the form of clips for this we do not find them introductions and crying home only Rarely, we found examples of Umayyad and Abbasid poets who adhere to the Talali heritage, so that they weep and pour their tears into it and flirt with some of them abandoning these traditions, and replacing them with the description of palaces, riads and flowers, especially in the Abbasid era.